Memorandum from GC to General Secretaries of all affiliated trade unions, 2 May 1926, re:The Mining Situation (page 3)
1926-05-02 "Memorandum from GC to General Secretaries of all affiliated trade unions, 2 May 1926, re:The Mining Situation (page 3)" [g0696003.jpg], 2 May 1926